The Role of Modern Pedagogical Technologies in the Development of the Science of Pedagogy - Shakir Mamatalievich Urishov (Zien Journals, 2023)
In today's pedagogy, technology has a special place in changing the way education is delivered and experienced. It revolutionized teaching methods, expanded learning opportunities, and opened up new opportunities for both educators and students. Here we explore the different ways technology is impacting education.
Keywords: Internet; digital libraries; websites; traditional textbooks